Effectiveness of a nurse-led intensive home-visitation programme for first-time teenage mothers (Building Blocks): a pragmatic randomised controlled trial - Robling, Michael; Bekkers, Marie-Jet; Bell, Kerry; Butler, Christopher C.; Cannings-John, Rebecca; Channon, Sue; Corbacho Martin, Belen; Gregory, John W.; Hood, Kerry; Kemp, Alison; Kenkre, Joyce; Montgomery, Alan A.; et al. (Elsevier, 2016)
Background